Prevalence of Chronic Cor Pulmonale in Chronic Obstructive Pulmonary Disease Patients in a Teaching Hospital in Nepal (Journal of Institute of Medicine Nepal, 2019)
Introduction: Chronic obstructive pulmonary disease (COPD) is the most common cause of cor pulmonale. Cor pulmonale in COPD is associated with decreased survival, increased hospitalization and mortality. In this study we aim to find out the prevalence of chronic cor pulmonale in COPD patients which would help in prevention of right sided heart failure and improve patients’ quality of life.Methods: This was a cross sectional observational study done in Kathmandu Medical College Teaching Hospital, Nepal. 50 COPD patients above the age of 30 years attending the outpatient department or admitted in wards were included. All COPD patients diagnosed by pulmonary function test (PFT) were assessed for cor pulmonale by echocardiography (ECHO). The demographic data, chest X-ray, PFT, electrocardiography (ECG) and ECHO findings were recorded, entered and analyzed using SPSS software, version 17.Results: Most of the patients enrolled in the study were between age group of 51-60 with female preponderance. 68% of the COPD patients had chronic cor pulmonale. Out of 21 male, 76.2% and out of 29 female COPD patients, 62.06% had cor pulmonale. Cor pulmonale was present in 53.12% and 94.4% of patients who had COPD for < 10 years and ≥10 years duration respectively. Cor pulmonale was present in 76% patients with severe COPD, 75% of patients with moderate COPD, 64.2% patients with very severe COPD and none of the patients with mild COPD. Pulmonary hypertension (PH) was present in 67.64% of cor pulmonale patients.Conclusion: The prevalence of chronic cor pulmonale in COPD patients was 68%. It was more in male patients, highest in patients with severe COPD, and the prevalence increased with duration of COPD. PH was present in 67.64% of cor pulmonale patients.